Contribution of Local Content Learning in Preserving Kajang Tribe Culture : Phenomenological Study - Kadir, Irsan; Kaharuddin, Kaharuddin; Firdaus, Firdaus; Sari, Nurindah (Jurnal Paedagogy, 2024)
This research aims to accumulate the concept of formal education in encouraging and maintaining the existence of the Kajang tribe’s cultural traditions. The research approach used is a qualitative with a phenomenological method. The informants in this study were the Kajang tribal leaders, the community, parents of students, and teachers of SDN 351 Kawasan Amma Toa. Data collection techniques used were through observation, interviews and documents. The data obtained were then analyzed through three stages, namely data reduction, data presentation and drawing conclusions. The results of the research show that "Pasang Ri Kajang" or noble values implemented in local content learning from the local wisdom of the Kajang tribal community are: 1) Love for God and the universe and its contents, 2) Responsibility, discipline and independence, 3) Honest, 4) Obey applicable rules and be polite, 5) Care about the environment, 6) Work hard in nature conservation, 7) Justice, 8) Be humble, 9) Love peace and unity. The integration of local wisdom values in learning will be in accordance with the existing environment experienced by students so that students will be more motivated in learning so that it will have an impact on preserving Kajang tribal culture.